JOANNA SASSOON, Agents of Empire: How E.L. Mitchell’s Photographs Shaped Australia - Hamilton-Hobbs, Emma (Archivaria, 2018)
Agents of Empire: How E.L. Mitchell’s Photographs Shaped Australia. Joanna Sassoon. North Melbourne: Australian Scholarly Publishing, 2017. x, 260 pp. ISBN 978-1-925333-73-2